Exploring the Application of High-Road Transfer in the Teaching of “Double Angle Bisector Modeling” Problem Solving - Chenchen Ma; Xiaochou Dai; Xinchao Li; Huiru Chen (Journal of Advanced Research in Education, 2025)
In the current teaching practice of junior middle school mathematics, teachers tend to directly teach the conclusion of geometric models, focusing on the training of low-road transfer, which leads to students’ difficulty applying the model flexibly to solve problems. In order to change this situation, the teaching of geometric model problem solving should be optimized based on the law of high-road transfer. Specific measures include: digging deep into the principles behind the model to help students identify the general principles and logical structure; establishing a model thinking framework by sorting out the internal logic of the mathematical model; and designing variations of practice questions to consolidate and deepen students’ understanding and to achieve the ability of high-road transfer. In this paper, for the problem-solving teaching of “double angle bisector modeling”, we give a high-road transfer path, refine the core ideas of the model and establish the solution ideas of related problems, so as to provide reference for the optimization of junior high school mathematics problem-solving teaching.